2006
DOI: 10.1177/1046496405285458
|View full text |Cite
|
Sign up to set email alerts
|

The Big Five Personality Traits and Individual Satisfaction With the Team

Abstract: Relationships between team composition in terms of team members' Big Five personality traits and individual satisfaction with the team after project completion were researched. Questionnaires were filled out by 310 undergraduate students ( N= 68 teams) working on an engineering design assignment. Individual satisfaction with the team was regressed onto individual, dissimilarity, and interaction scores. A positive main effect was found for individual agreeableness and emotional stability and for dissimilarity i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
84
0
10

Year Published

2007
2007
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(95 citation statements)
references
References 57 publications
(82 reference statements)
1
84
0
10
Order By: Relevance
“…In addition, participants' grade point average (GPA) was recorded (as a control variable). Satisfaction from the Group was assessed with three items, taken from Peeters et al (2006): ''If I ever have to participate in a similar project, I would like to do it with this group''; ''Overall, I was satisfied with the composition of our group''; ''In general, the proceedings of the group were done in a pleasant atmosphere.'' The items were selected because they assess participants' satisfaction from the group as a measure of the group's perceived effectiveness.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, participants' grade point average (GPA) was recorded (as a control variable). Satisfaction from the Group was assessed with three items, taken from Peeters et al (2006): ''If I ever have to participate in a similar project, I would like to do it with this group''; ''Overall, I was satisfied with the composition of our group''; ''In general, the proceedings of the group were done in a pleasant atmosphere.'' The items were selected because they assess participants' satisfaction from the group as a measure of the group's perceived effectiveness.…”
Section: Methodsmentioning
confidence: 99%
“…In a study of student work groups, greater satisfaction with the team was associated with higher mean levels of agreeableness and emotional stability, and greater similarity in conscientiousness (Peeters, Rutte, Van Tuijl, & Reymen, 2006b). This study also found that greater dissimilarity in extraversion was associated with lower levels of satisfaction but only for those team members with low levels of extraversion (a mean-variance interaction effect).…”
Section: Social Interactions and Group Dynamicsmentioning
confidence: 98%
“…The Big Five traits have been found to be related to individual-level outcomes such as happiness, physical and psychological health, spirituality, and identity; interpersonal-level outcomes such as quality of relationships with peers, family, and romantic others; and organizational-or sociallevel outcomes such as occupational choice, satisfaction, performance, community involvement, criminal activity, and political ideology (for a comprehensive review, see Ozer & Benet-MartĂ­nez, 2006). These personality traits have also been found to be positively related to entrepreneurship (Zhao & Seibert, 2006), cultural intelligence (Ang, Van Dyne, & Koh, 2006), and satisfaction with teams (Peeters, Rutte, van Tuijl, & Reymen, 2006) and negatively associated with undesirable outcomes such as burnout (Bakker, van der Zee, Lewig, & Dollard, 2006).…”
Section: The Big Five Personality Traitsmentioning
confidence: 99%